A hybrid algorithm for solving inverse boundary problems with respect to intermediate masses on a beam - Aniyarov, A.A.; Jumabayev, S.A.; Nurakhmetov, D.B.; Kussainov, R.K. (Bulletin of the Karaganda University. Mathematics Series, 2021)
The inverse problem of determining the weight of three intermediate masses on a uniform beam from the known three natural frequencies has been solved. The performed numerical analysis allows restoring the value of only the second mass in a unique way. The inverse problem of determining the weight of three intermediate masses is solved uniquely except in the case when the first and the third masses are located geometrically symmetric relative to the middle of the beam. The hybrid algorithm for the unique solving inverse problem of determining the weight of three intermediate masses has been developed. The first three natural frequencies of the beam are calculated numerically by using the Maple computer package. Analytical relations between the masses are found.